Coming home : the Baxter family : a story of undying hope - Kingsbury, Karen (Grand Rapids, MI : Zondervan, 2012)
As the Baxter's make plans to come together for a summer lakeside reunion, the unthinkable happens. When the family rallies together, memories come to light that bring healing and hope during a time when darkness might have the final word. From bestselling author Karen Kingsbury, Coming Home---a stand-alone novel---can serve as either a grand introduction or a beautiful conclusion in the saga of the Baxter Family.
Keywords: Christian fiction